Body temperature and cardiovascular control during exercise in the heat: implications for special populations and athletic performance - Wang, H. (Louisiana State University and Agricultural and Mechanical College, The School of Kinesiology, 2020)
Exercise in the heat increases the risk of dehydrationand hyperthermia, subsequently impaired cardiovascular function and increased thermal stress. The purpose of this dissertation is to determine the fluid balance,cardiovascular function, thermoregulation, and cooling intervention during exercisein the heat. Four novel studies were conducted in this dissertation.The first and second studiesinvestigated the fluid balance during exercise in the heatacrossdifferent sports with theirspecial concerns.The first study conducted in female soccer,suggestingmost players were in a hypohydration state after practice, andvarious fluid needs were exhibited by different positions, possibly associated with on-field physical exertion characteristics. The second study was a longitudinal study examining the physiological and hematological responses of football players with sickle cell trait(SCT).SCTexhibited ~37% of hemoglobin Sand hada greater serum uric acid concentration and red blood cell distribution width. Furthermore, SCThad 14% less distance ran on the field across the same intensity compared to position-matched controls. These two hydration studies provided the applicable information for teams to promote hydration guidelinesand better monitor biomarkers in SCTduring exercise in the heat. The third and fourth studies examined the effects of cooling interventions on lowering body temperature and thermal stress. The third study was a pilot study to examine the effects of leg cooling on soccer-simulated intermittent exercise performance. The results suggested leg cooling loweredthigh skin temperatureby 4.3°Cand was effective to decrease auditory canal temperature, core temperature, and thermal sensation. Tissue saturation index was not changed, suggesting muscle blood flow was not affected in this cooling treatment.The last study in the heat with or without simulated wind. The results suggestedthe novel shirt with thecooling fan exhibited a superior upper-body heat dissipation during exercise in the heat, mainly decrease averaged skin temperature, ratings of perceived exertion, and promote subjectiveoverall feeling. Given these two cooling studies above,we provided the noticeable applicationsin external cooling method and clothing material factor to decrease body thermal stress.